Kartlegging av astmaundervisning til barn og foreldre i barneavdelinger mellom 2004, 2006 og 2014 - Anne Trollvik; Liv-Grethe Kristoffersen Rajka; Gun Nordström (Septentrio Academic Publishing, 2017)
The aim of the study was to investigate the organization of asthma education for children and parents in children's wards in Norway over a ten-year period and how Ane and Bronky teaching material has been implemented. A prospective cross-sectional study using a questionnaire was conducted in 28, 22 and 29 children's wards in 2004, 2006 and 2014. The response rate varied between 86 percent and 97 percent. Statistical analysis by means of Fisher's exact test was used. The findings revealed that organized asthma education for children increased between 2004 and 2006, while it decreased in 2014. Dialogue and demonstration were common teaching methods. User participation in teaching sessions increased between 2004 and 2006. Only half of the wards reported that asthma education was the responsibility of management to a large/very large extent. This presents future challenges in establishing, prioritizing and ensuring stability in health education for children and their families.